Comparison of laparoscopic cystectomy and purse-string suture technique in the surgical treatment of ovarian dermoid cysts - Atilgan, Remzi; Pala, Şehmus (My University, 2020)
Introduction: This study is a comparison of the outcomes of 2 cystectomy modalities in the surgical treatment of ovarian dermoid cysts.Materials and Methods: The intraoperative and postoperative results of 44 ovarian dermoid cyst patientswho underwent surgical treatment between 2012 and 2019 using 2 different methods were compared. Thestudy population was divided into 2 groups: Group 1 (n=21) underwent cystectomy using the purse-stringsuture method via mini-laparotomy and Group 2 (n=23) underwent laparoscopic cystectomy.Results: The mean ovarian cyst diameter was 11 cm in Group 1 and 6 cm in Group 2. The diameter of the cystwas significantly larger in Group 1 than in Group 2. The duration of the operation was significantly shorter inGroup 1 than Group 2 (45 min. vs. 70 min.). The intraoperative rupture rate was significantly lower in Group1 compared with Group 2 (4.7% vs. 30%). Chemical peritonitis did not develop in either group. The durationof hospitalization was similar between the groups. The recurrence rate was significantly lower in Group 1than Group 2 (0% vs. 21%).Conclusion: For clinicians who do not have the optimal conditions or surgical experience for a laparoscopicoperation, and particularly for large ovarian dermoid cysts, the cystectomy technique performed using apurse-string suture via a mini-Pfannenstiel incision can be an effective treatment method.
Keywords: Kadın Hastalıkları ve Doğum; Genel ve Dahili Tıp; Patoloji; Cerrahi